Exosomes secreted by cardiomyocytes subjected to ischaemia promote cardiac angiogenesis - Ribeiro-Rodrigues, Teresa M. (2017)
Funding Information: This work was supported by European Regional Development Fund (FEDER) through the Operational Program for Competitiveness Factors (COMPETE) [HealthyAging2020 CENTRO-01-0145-FEDER-000012-N2323, POCI-01-0145-FEDER-016385, POCI-01-0145-FEDER-007440 to CNC.IBILI, POCI-01-0145-FEDER-007274 to i3S/INEB and NORTE-01-0145-FEDER-000012 to T.L.L.]; national funds through the Portuguese Foundation for Science and Technology (FCT) [PTDC/SAU-ORG/119296/2010, PTDC/ NEU-OSD/0312/2012, PESTC/ SAU/UI3282/2013-2014, MITP-TB/ECE/0013/ 2013, FCT-UID/NEU/04539/2013], PD/BD/52294/2013 to T.M.R.R., SFRH/ BD/85556/2012 (co-financed by QREN) to V.C.S]; Lisboa Portugal Regional Operational Programme (LISBOA 2020) and Norte Portugal Regional Operational Programme (NORTE 2020), under the PORTUGAL 2020 Partnership Agreement; and by INFARMED Autoridade Nacional do Medicamento e Produtos de Saúde, I.P. [FIS-FIS-2015-01_CCV_20150630-157]. Publisher Copyright: © 2017 The Author.